Pendampingan Pengganggaran dan Pengawasan Keuangan pada UMKM dan NGO Binaan - Khairunnisa, Khairunnisa; Aminah, Wiwin; Fahlevi, Ali Riza; Arfista, Fajra; Qodrio, Anjelina (STIE Bina Karya, 2024)
Budgeting and oversight are essential for ensuring the sustainability and effectiveness of non-profit organizations (NGOs). This process includes thorough financial planning, strategic resource allocation, and careful monitoring to guarantee that funds are used to support the organization’s mission. In the budgeting process, the involvement of various stakeholders—such as the board of directors, executive directors, financial managers, and program heads—is crucial for creating a realistic budget that meets the organization’s needs. Additionally, effective budget oversight is vital for ensuring transparency, accountability, and efficiency, which are core values in NGO management. A practical approach to budgeting involves identifying strategic priorities, projecting revenues, and evaluating expenditures in relation to the organization’s programs and operations. Good budget oversight includes monitoring progress, analyzing the discrepancies between planned and actual results, and implementing corrective measures when necessary. With effective budget management, NGOs can enhance their credibility in the eyes of donors, ensure the smooth implementation of programs, and reduce financial risks that could impede the achievement of their goals. This study highlights the significance of a transparent and accountable budgeting and oversight system in promoting the sustainability and effectiveness of NGOs. In conclusion, an integrated and data-driven approach to budget preparation and monitoring strengthens financial governance and enhances the social impact of the programs implemented.